Roadmap for additive manufacturing of HAYNES® 282® superalloy by laser beam powder bed fusion (PBF-LB) technology. (June 2021) - Otto, Robert; Brøtan, Vegard; Carvalho, Patricia A.; Reiersen, Magnus; Graff, Joachim S.; Sunding, Martin F.; Berg, Olav Åsebø; Diplas, Spyros; Azar, Amin S.
Abstract: Although various alloy systems have been explored for additive manufacturing (AM) during the past decade, introducing a new alloy remains a challenging task. Most of the materials require iterative builds, for investigating numerous parameters and determining a viable and repeatable process window. Among the challenging yet highly demanded materials, Haynes 282 superalloy was chosen. It was initially processed through conventional density cube approach, by varying the process parameters for each processed cube. Although the relative densities of the initial builds were not dramatically low, micro-cracks were present in all of them, mostly evolved on a selective number of grain boundaries and spanning only across a single laser path. Detailed modelling and advanced characterization techniques were employed to understand the root cause and cracking mechanism. It was found that the grain boundary precipitates are responsible for crack initiation, amid stress gradient across the grain boundary due to the adjacent grain orientations. Therefore, the failure mechanism is determined as ductility-dip cracking. Based on the findings, a new process window was defined using elevated temperature and novel scanning strategy. No cracks were observed under the modified processing window, meaning that the material can reliably be processed by laser beam powder bed fusion (PBF-LB). Graphical abstract: Unlabelled Image Highlights: A comprehensive approach was introduced for investigating the root cause of material failure under AM conditions. HAYNES® 282® (H282) superalloy was investigated as a new material for laser beam powder bed fusion (PBF-LB) technology. Precipitation- and residual stress control under recurrent thermal cycles are key to success in PBF-LB processing of H282. Heated build platform to 300 °C and novel scan strategy results in low porosity and micro-crack free material. Hot isostatic pressing recrystallizes the microstructure, eliminates porosity and heals the micro-cracks.